If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -4x = 42 Solving 10 + -4x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -4x = 42 + -10 Combine like terms: 10 + -10 = 0 0 + -4x = 42 + -10 -4x = 42 + -10 Combine like terms: 42 + -10 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| 7+1.5x-17-5.5x= | | -3x^2+12x=15 | | 3ln(x-3)=6 | | 81^(3/2)=x | | 81=3x-4(6x+6) | | 80x=16800 | | -16+2x=12-10x | | 10m+30=60 | | ln(2x-5)+3=9 | | 81^(2/3) | | 2x+6(2x-12)=-170 | | (2x+22)+(2x+22)+2x=80 | | iz^2-2*z+1-i=0 | | (60/x-2)-60/x=1 | | 14x+25=6x+153 | | -3x+(-5)=28 | | 15x+18=54 | | 65(x+2)=90 | | 85=4x-7(2x-5) | | x=9/3 | | 3x-5=11-5x | | x-6+2y-5+z=18-x+3y-11+z-4 | | 3x-5=-5x | | 3x/5=11/5x | | 3+55x=44x+11 | | Y+2x+1=0 | | 20-17y=12.52 | | 4y+2=y | | 4x+44=80 | | 3y^2-9x+12=0 | | x-6+2y-5+z=17 | | x^4-635= |